Pengaruh Model Pembelajaran Tactical Games Dalam Permainan Bola Basket Siswa SMA Negeri 1 Cibitung - Afrizal, Fauzan Noer; Lavayet, Havzy; Shanna, Gladys (Jurnal Ilmiah Wahana Pendidikan, 2023)
AbstractThis research aims to investigate the influence of the Tactical Games learning model in basketball on high school students. The learning model is designed to enhance the understanding of tactics and teamwork in the context of basketball games. The results of the research indicate that the use of the Tactical Games learning model has a positive impact on high school students in basketball. Tactical Games learning provides students with opportunities to learn actively, participate in game-like situations similar to real conditions, and apply tactical strategies in competition.